Metal organic framework-derived CoMn2O4 catalyst for heterogeneous activation of peroxymonosulfate and sulfanilamide degradation - Li, Chen-Xuan; Chen, Chang-Bin; Lu, Jia-Yuan; Cui, Shuo; Li, Jie; Liu, Hou-Qi; Li, Wen-Wei; Zhang, Feng (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •Plate-shaped CoMn2O4 was synthesized using MOFs as precursor.•The catalyst showed large specific surface area and abundant active sites.•It had much higher catalytic activity than previously-reported CoMn2O4 catalyst.•The Co-Mn synergy in heterogeneous catalysis were elucidated.•The material showed good stability and reusability for SA removal. Spinel-type CoMn2O4 materials are promising catalyst for heterogeneous activation of peroxymonosulfate (PMS), but the catalytic activity still need considerable improvements for practical environmental application and the underlying Co-Mn synergy is unclear. In this work, we synthesized CoMn2O4 microplates by using CoMn2-perylene-3,4,9,10-tetracarboxylic dianhydride (ptcda) metal organic frameworks (MOFs) as the precursor. The resulting material showed significantly higher catalytic activity for the PMS activation and sulfanilamide (SA) degradation than the CoMn2O4 obtained by conventional solvothermal synthesis methods, due to its much higher specific surface area and abundant surface hydroxyl groups as the active sites. In addition, the Co-Mn synergy in the synthesized material for the efficient heterogeneous catalysis was elucidated. The catalyst stability was also evaluated. Our work may lay the foundation for optimized design of highly-efficient heterogeneous catalyst for environmental application.